Defining the wheat quality requirements for Indian whole wheat chapatti - Fenton, Haelee Kim (Curtin University, 2012)
The ability of Australian wheat varieties, which had varying wheat qualities, to make the Indian unleavened flat bread chapatti was investigated. Flour and chapatti quality of the Australian wheat varieties was characterised and benchmarked against Indian wheat varieties. The research provided insight into the important flour quality, chapatti quality and chapatti making methodology needed for future selection of Australian wheat for the Indian market.